PHYTOCHEMICAL SCREENING, ANTIOXIDANT AND ANTIBACTERIAL ACTIVITIES OF MILLINGTONIA HORTENSIS (L) - A., Janaki; K., Kaleena P.; D., Elumalai; P., Hemalatha; M., Babu; K., Velu; Ravi, Sudha (International Journal of Current Pharmaceutical Research, 2017)
Objective: Millingtonia hortensis Linn (Bignoniaceae) is commonly known as cork tree and Akash neem. Aim of studies to determine the antioxidant activity and antibacterial activity. Methods: The antioxidant activity of different solvent extracts were measured by chemical analyses involving the assay of 1,1-diphenyl-2-picryhydrazyl (DPPH) radical scavenging activity and super oxide radical scavenging activity. Results: Phytochemicals (secondary metabolites) screening of methanol, chloroform, ethanol, petroleum ether, aqueous leaf extracts revealed the presence of carbohydrates, tannins, saponins, flavonoids, alkaloids, betacyanins, phenols and coumarins. Conclusion: The presence of these phytochemicals and antioxidant capacity support the use of this plant as an antibacterial agent against the group of micro organisms tested. Â 